Faith-Based Financing and Community Mobilization: A Qualitative Study of Madrasah Sustainability in Aceh Besar - Safriadi; Syafruddin; Ahmad Faizuddin; Wina Rahmayani; Muhammad Rizki (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Madrasahs in Indonesia frequently face financial limitations due to minimal government support, unlike public schools that rely heavily on state funding. This condition demands that madrasahs become more independent and innovative in sourcing financial support, particularly through active community participation. This study aims to analyze the sources of community-based financing and the role of Islamic philanthropy in sustaining madrasah education. The research focuses on two senior Islamic schools Madrasah Aliyah Teungku Chiek Oemar Diyan and Al Manar within Islamic boarding schools in Aceh Besar District. A qualitative field research approach was employed, utilizing semi-structured interviews, direct observation, and document analysis. Findings reveal that the primary sources of financing include contributions from students’ parents, the general community, educational foundations, self-managed pesantren enterprises, and Islamic philanthropic resources such as zakat, infaq, sadaqah, and waqf. These financial sources are managed under principles of transparency, internal and external accountability, and ethical governance. Such management practices have led to enhanced community trust and increased participation in madrasah development. This study concludes that community-based financing, when supported by faith-driven values and transparent administration, presents a sustainable model for improving madrasah quality, especially in regions with limited government budget allocations for Islamic education.